Esferas de goma do cajueiro e quitosana para liberação de fármacos - Magalhães Júnior, Guilherme Augusto (2007)
Cashew gum based beads were produced through interpenetrating polymer networks and polyelectrolyte complexation techniques. Beads of chitosan (CH) and cashew gum (CG)/CH were further crosslinked with genipin obtained from “genipapo” fruits. This crosslinking agent was characterized by proton and carbon nuclear magnetic resonance and infrared spectroscopy. Beads of CH and CH/CG were doped with sodium diclofenac and characterized by Fourier Transform Infrared spectroscopy and Electron Microscopy. Beads degree of swelling and the drug release kinetics were also determined. It was found that CH/CG beads contained up to 83 % CG and maximum swelling occurred at pH 1.2. The higher the crosslinking density, the lower were the swelling degree and the diffusion coefficient. Moreover, drug release was also found to decrease with increasing crosslinking density and no drug release occurred at pH 7.4 for CH/CG beads crosslinked with genipin, although non-crossliked bead did release the drug at that pH. CH/CG beads drug release was found to follow a non-Fickian mechanism. Polyelectrolyte complexes of chitosan and carboxymethylated cashew gum (CCM) in beads form were also investigated regarding the effects of molar mass and degree of substitution of CCM on the swelling degree and on bovine serum albumin (BSA) release. Data obtained revealed that both of molar mass and degree of substitution affect beads swelling degree and water diffusion coefficient.